Dynamics for a stochastic delayed SIRS epidemic model - Shi, Xiangyun; Cao, Yimeng; Zhou, Xueyong (Nonlinear Analysis: Modelling and Control, 2020)
In this paper, we consider a stochastic delayed SIRS epidemic model with seasonal variation. Firstly, we prove that the system is mathematically and biologically well-posed by showing the global existence, positivity and stochastically ultimate boundneness of the solution. Secondly, some sufficient conditions on the permanence and extinction of the positive solutions with probability one are presented. Thirdly, we show that the solution of the system is asymptotical around of the disease-free periodic solution and the intensity of the oscillation depends of the intensity of the noise. Lastly, the existence of stochastic nontrivial periodic solution for the system is obtained.
Keywords: stochastic SIRS epidemic model; extinction and persistence; periodic solution; time delay